Zeolit sebagai bahan pengisi pada kompon karet ditinjau dari sifat fisika vulkanisatnya - Penny Setyowati (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2002)
Zeolities are natural rock found in a large – scale in Indonesia and it can be used as rubber and plastic filler. In this research, mordenite zeolite was used as a rubber compound filler at 50 – 100 phr (per hunddreed rubber) variation and with High Abrasion Furnace (HAF) black and minarex oil combination by 10/6 and 20/8 ratio. The aim of the research was to study the influence of zeolite in rubber compound, concerning to physical properties of the vulanicase. The effect of zeolit addition on rubber compound was a decrease in the tension break 13.85-15.33%, the elongation break 9.5-12 %, the tear resistance 9.1-23.1 % and the abrasion resistance 15.75-23.95% of the volcanicase, while the hardness was increase 10 %. Decreasing of such physical properties can be prevent by mixing it with HAF black and minarex oil combination. The best result was reached at application of zeolite 50 phr with HAF black and minarex oil combination. . Key words : Zeolit, rubber, filter.